1996
DOI: 10.1136/thx.51.11.1115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of upper respiratory tract infections in patients with cystic fibrosis.

Abstract: Background -The polymerase chain reaction has improved the detection of picornaviruses and rhinoviruses and our understanding of their role in reversible airways disease. The effects of colds on lower respiratory morbidity and bacterial colonisation in cystic fibrosis remain uncertain. Methods -Children with cystic fibrosis were evaluated regularly in the clinic and the parents notified the investigators when their child developed a cold. Nasopharyngeal specimens were collected at the start of the infection fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
138
3
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(153 citation statements)
references
References 27 publications
4
138
3
5
Order By: Relevance
“…Recently, it has been found that detection of rhinovirus could be improved by up to five times using PCR [14,23]. Thus, using PCR, rhinovirus has been shown to be the predominant virus, associated with 50% of asthmatic exacerbations in children and 33% in adults and 19% of exacerbations of cystic fibrosis, with smaller proportions of exacerbations attributed to other viruses [6,18,24]. Using limiting dilutions of human rhinovirus 14, the PCR used in the present study has been shown to have a detection limit of 1610 3 median tissue culture infective doses .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that detection of rhinovirus could be improved by up to five times using PCR [14,23]. Thus, using PCR, rhinovirus has been shown to be the predominant virus, associated with 50% of asthmatic exacerbations in children and 33% in adults and 19% of exacerbations of cystic fibrosis, with smaller proportions of exacerbations attributed to other viruses [6,18,24]. Using limiting dilutions of human rhinovirus 14, the PCR used in the present study has been shown to have a detection limit of 1610 3 median tissue culture infective doses .…”
Section: Discussionmentioning
confidence: 99%
“…RVs are single-stranded RNA viruses responsible for the majority of upper respiratory tract infections and their complications, including otitis media, sinusitis, and bronchitis. By a sensitive detection method (polymerase chain reaction), RV was detected in 25.6% of viral-induced acute otitis media (1), and up to one-half of all viral-associated COPD and CF exacerbations (4)(5)(6)(7)9). In each of these conditions, coinfection of RV and bacteria are thought to play an important pathogenetic role.…”
mentioning
confidence: 99%
“…The coinfection of viruses and bacteria have been recognized in several respiratory diseases including pneumonia, otitis media (1-3), chronic obstructive pulmonary disease (COPD) (4-7) and cystic fibrosis (CF) (8)(9)(10)(11). Viruses predispose the host to bacterial infection by various mechanisms including destruction of the respiratory epithelium, modulation of innate defenses, and alteration of cell membranes, which in turn facilitates bacterial adherence.…”
mentioning
confidence: 99%
“…During the last decade, RV has been associated with exacerbations in pediatric and adult asthma patients, and in patients with cystic fibrosis and bronchopulmonary dysplasia. 11,[21][22][23] It is essential for understanding of physiopathological mechanisms of this disease to answer the question of whether RV can cause AB by establishing a lower airway infection or if it is associated with the condition by indirect mechanisms. Papadopoulos et al 13 demonstrated that RV is capable of causing lower airway infection in healthy adults and those with asthma.…”
Section: Discussionmentioning
confidence: 99%